Mencari Agama Baru (Studi Terhadap Munculnya Sekte-Sekte Agama) - Waryono Abd. Ghofur (Al-Jami'ah: Journal of Islamic Studies, 1998)
Every religion   born in the society always has its own attraction and fascination, especially if they are seen from the outward perspective of the religion. The fascination offered by the religion is basically promised claims   or doctrines which give a covenant as well to their adherents. one thing   that   psychologically can fulfill people's desire and makes him satisfied to live in and together with it. They   are fascination   and claims   which   become   "religious languages” capable of making    religious society.  If in its historical journey, the religion losses its vital vigor as a hope giver for its religious society as promised, there will be a dissatisfaction.   In other words, the religion which   has lost   its function so as to fail to accommodate the adherent's interest and hopes will be left behind by its devotions.  One of initial attitudes showed and born with his condition is protest and critic movements toward the religion. The birth and appearance of sect is an accretion of such a protest movement.   Here, a sect   is   basically an integral of a big religious group trying to separate   itself from the hegemony of the majority. Therefore, although   the sect   is   still a part of a big religious society, it has different religious experience and system.  Due to this distinctiveness, a certain sect is frequently identified as a splinter   group. Hence, in an extreme way a sect can be said as a religion in a religion or a "small religion" in a "big religion'.  It is here also that a sect may be called as a''son of religion.'